Stress and locus of control among Singaporean trainee special education teachers - Bimal Rai. (2008)
Thirty-one trainee special education teachers completed the Teacher Stress Inventory and the Teacher Locus of Control Scale in a study that was primarily aimed to investigate the relationship between these trainee teachers' self-perception of work stress and their locus of control.